2019
DOI: 10.3389/fpsyg.2019.02504
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Uncertainty and Affect

Abstract: Uncertainty and affect are fundamental and interrelated aspects of the human condition. Uncertainty is often associated with negative affect, but in some circumstances, it is associated with positive affect. In this article, we review different explanations for the varying relationship between uncertainty and affect. We identify “mental simulation” as a key process that links uncertainty to affective states. We suggest that people have a propensity to simulate negative outcomes, which result in a propensity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
181
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(195 citation statements)
references
References 135 publications
(216 reference statements)
9
181
0
5
Order By: Relevance
“…We interpreted this evidence proposing that more attentional resources were oriented on the pleasant sensory features of musical intervals rather than on the motor response. In accordance with neurophysiological evidence collected in humans and in rodents, it has been suggested that our nervous system is equipped with a "Behavioural Inhibition System", activated by novel, unexpected events and actively hindering behavioural responses, thus allowing the individual to re-plan an adequate motor response (Anderson et al, 2019). In other words, we suggest that the ultimate product of aesthetic experience may not be an approach reaction, but a simple enhancement of the perceptual activity per se (Kirsch, Urgesi & Cross, 2016).…”
Section: Contemplation Of Beauty and Motor Inhibitionsupporting
confidence: 83%
“…We interpreted this evidence proposing that more attentional resources were oriented on the pleasant sensory features of musical intervals rather than on the motor response. In accordance with neurophysiological evidence collected in humans and in rodents, it has been suggested that our nervous system is equipped with a "Behavioural Inhibition System", activated by novel, unexpected events and actively hindering behavioural responses, thus allowing the individual to re-plan an adequate motor response (Anderson et al, 2019). In other words, we suggest that the ultimate product of aesthetic experience may not be an approach reaction, but a simple enhancement of the perceptual activity per se (Kirsch, Urgesi & Cross, 2016).…”
Section: Contemplation Of Beauty and Motor Inhibitionsupporting
confidence: 83%
“…Also, volunteers had an uncertain assignation of workload per day, generating high levels of tension. This agrees with Carleton [11], Anderson et al [2], Lake and LaBar [29], as these kinds of assignments could lead to anxiety depending on the uncertainty of the weekly number of patients and their needs.…”
Section: Categoriessupporting
confidence: 85%
“…Interestingly, information about the number of reported cases of COVID-19 and the analysis of the COVID-19 pandemic were negatively associated with anxiety. We reasoned that knowing the number of reported cases and deaths could actually lower the uncertainty level of the public because uncertainty often arises with lack of information and "uncertainty is experienced subjectively as anxiety" [15]. Compared to not knowing the real situation of the pandemic, people are likely to feel less anxious when they get to know more information about the seriousness of the pandemic through media.…”
Section: Discussionmentioning
confidence: 99%